PROBLEMS IN USING INNOVATIVE EDUCATIONAL TECHNOLOGIES IN TEACHING THE SCIENCE OF MOLECULAR GENETICS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article analyzes the problems of applying innovative educational technologies to the science of molecular genetics and provides information on ways to solve them.